The potential of indigenous Bacillus sp. BT3.1 as an antifungal biopesticide against the plant pathogen Fusarium oxysporum - FARAH AISYAH NAFIDIASTRI; NATASYA THESSA LOLITA; HANA SHAFIYAH RIQINA; BELLA ZEZARI AURORA; ALMANDO GERALDI; TRI NURHARIYATI; AGUS SUPRIYANTO; NI’MATUZAHROH NI’MATUZAHROH; FATIMAH FATIMAH; SALAMUN SALAMUN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nafidiastri FA, Lolita NT, Riqina HS, Aurora BZ, Geraldi A, Nurhariyati T, Supriyanto A, Ni’matuzahroh, Fatimah, Salamun. 2024. The potential of indigenous Bacillus sp. BT3.1 as an antifungal biopesticide against the plant pathogen Fusarium oxysporum. Biodiversitas 25: 2679-2686. Biosurfactants are green surfactants that bacteria can produce, one of which is Bacillus. This genus can produce lipopeptide-type biosurfactants, namely surfactin, that can inhibit the growth of fungal pathogens. This research aims to determine the biosurfactant activity on molasses substrates and the antifungal activity of isolate BT3.1 against Fusarium oxysporum. The biosurfactant activity test method tested hemolytic activity using the spot method, surface tension analysis, and emulsification activity. In addition, an antifungal activity test was also carried out using the swab method. Characterization of isolate BT3.1 was carried out macroscopically and microscopically. The macroscopic characteristics of isolate BT3.1 show that bacteria from the genus Bacillus are moderate in size, white, irregular with serrate colony edges, shiny raised elevations, and a shiny surface texture. Microscopic characteristics of the isolate showed Gram-positive bacteria with oval-shaped endospores in the center. Based on the results of the biosurfactant activity test, isolate BT3.1 showed beta-type hemolysis activity, reduced surface tension by 23.3 mN/m on distilled water and 12 mN/m on NB media, and produced an emulsion activity value of around 52%. The results of the production of crude extract of BT3.1 isolate on 2, 4, and 6% molasses substrates showed optimal biosurfactant activity at a concentration of 4% with an incubation time of 48 hours. The antifungal activity of isolate BT3.1 showed that 80% inhibited the growth of Fusarium oxysporum, so the indigenous bacteria Bacillus sp. BT-3.1 has the potential to be developed as a raw material candidate for antifungal biopesticides against the plant pathogen Fusarium oxysporum.